2013
DOI: 10.1007/s11051-013-2126-z
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-doped cerium oxide nanoparticles protect cells from hydrogen peroxide-induced apoptosis

Abstract: To develop new nanoparticle materials possessing anti-oxidative capacity with improved physical characteristics, we have studied titanium-doped cerium oxide (CeTiO2) nanoparticles. CeTiO2 nanoparticles had a mode diameter of 15-20 nm. These nanoparticles demonstrated catalase activity, and did not promote the activation of hemolytic or cytolytic pathways in living cells. Using surface plasmon resonance enhanced microscopy, we find that these nanoparticles associate with cells. Transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Anti-oxidative by scavenging the free radicals in the retina Pourkhalili et al, 2011 Decrease progression of diabetes reduce the level of oxidative damage by scavenging the free oxygen species due to diabetes Zhou et al, 2011 Alzheimer's disease titanium-doped 15-20 nm Contribute to deflecting tissue damage in a broad spectrum of oxidant-mediated diseases, such as macular degeneration and Alzheimer's disease. Clark et al, 2013 Potential application of the nano-ceria in the medicine…”
Section: Human Cell Linementioning
confidence: 99%
“…Anti-oxidative by scavenging the free radicals in the retina Pourkhalili et al, 2011 Decrease progression of diabetes reduce the level of oxidative damage by scavenging the free oxygen species due to diabetes Zhou et al, 2011 Alzheimer's disease titanium-doped 15-20 nm Contribute to deflecting tissue damage in a broad spectrum of oxidant-mediated diseases, such as macular degeneration and Alzheimer's disease. Clark et al, 2013 Potential application of the nano-ceria in the medicine…”
Section: Human Cell Linementioning
confidence: 99%
“…This was done using a model of hydrogen peroxide induced oxidative stress. As shown previously, this model can be used to provide an adequate assessment of the therapeutic potential of cerium oxide nanoparticles. , We used higher concentrations of hydrogen peroxide (1.5 mM for 30 min), in comparison with previous reports, , to demonstrate high catalase-like activity of encapsulated nanoceria.…”
Section: Resultsmentioning
confidence: 99%
“…[ 164 ] This study demonstrated no change in the CAT‐like activity of CeTiO 2 NPs following incubation in culture medium. [ 165 ] As such, this area of rNZ–corona research warrants further investigation. Under healthy physiological conditions, cells, and proteins maintain a reduced state, and it is conceivable that the presence of oxidizing rNZs may disrupt this balance by depleting electrons from aqueous redox proteins and/or redox couples, or by acting as catalysts.…”
Section: Reducible Nanozymes and The Primary Principles That Drive Di...mentioning
confidence: 99%